Results of Seismological Monitoring in the Cascade Range, 1962-1989: Earthquakes, eruptions, avalanches and other curiosities - Weaver, C.; Norris, R.; Trisler, C. (Geoscience Canada, 1990)
Summary Modern monitoring of seismic activity atCascade Range volcanoes began at Longmire on Mount Rainier in 1958. Since then, there has been an expansion of the regional seismic networks in Washington, northern Oregon and northern California. Now, the Cascade Range from Lassen Peak to Mount Shasta in the south and Newberry Volcano to Mount Baker in the north is being monitored for earthquakes as small as magnitude 2.0, and many of the strato volcanoes are monitored for non-earthquake seismic activity. This monitoring has yielded three major observations. First, tectonic earthquakes are concentrated in two segments of the Cascade Range between Mount Rainier and Mount Hood and between Mount Shasta and Lassen Peak, where as little seismicity occurs between Mount Hood and MountShasta. Second, the volcanic activity and associated phenomena at Mount St. Helens have produced intense and widely varied seismicity. And third, at the northern strato-volcanoes, signals generated by surficral events such as debris flows, icequakes, steam emissions, rockfalls and icefalls are seismically recorded. Such records have been used to alert authorities of dangerous events in progress.